Worker health and safety on offshore wind farms (Special report (National Research Council (U.S.). Transportation Research Board) ;, 2013)
"TRB Special Report 310: Worker Health and Safety on Offshore Wind Farms examines the hazards and risks to workers on offshore wind farms on the outer continental shelf as compared with the hazards and risks to workers on offshore oil and gas operations. The report explores gaps and overlaps in jurisdictional authority for worker health and safety on offshore wind farms and evaluates the adequacy of--and recommends enhancements to--the existing safety management system (SMS) requirement published in 30 CFR 585.810. The study committee recommends that the U.S. Department of the Interior's Bureau of Ocean Energy Management (BOEM) adopt a full SMS rule for workers on offshore wind farms at a level of detail that includes the baseline elements identified in this report. An enhanced SMS rule should require the use of human factors engineering elements in the design process and should encompass all activities that the lessee and its contractors undertake. In collaboration with other regulatory agencies and industry stakeholders, BOEM should clearly define roles and responsibilities and indicate which standards could apply for all phases of wind farm development, regardless of jurisdiction. Also, with the help of stakeholders, BOEM should support the development of guidelines and recommended practices that could be used as guidance documents or adopted by referen"--Provided by publisher.